Impurity analysis of JET DiMPle pulses. (12th October 2021) - Lawson, K D; Coffey, I H; Rimini, F; Książek, I
Abstract: Divertor monitoring pulses (DiMPle) have been run in JET from the C35 campaign onwards. They provide an opportunity to study the impurity contamination of the plasma when it is limited by different surfaces within the machine, as well as the longer term behaviour of the impurities. In these discharges the plasma is first limited on the outer wall, then on the inner wall and, subsequently, in the X-point configuration the outer strike point is positioned on the horizontal tile 5 of the machine followed by tile 6 and then the vertical tile 7. The present study details the impurity behaviour in the DiMPle pulses from JET-ILW campaigns C35 to C38, which ran from 2015 to 2019. The impurities can largely be divided into two groups. The first, including most gases, are present immediately after their use in the machine; the second group includes those elements that are retained on plasma facing surfaces within the vessel. Most of these are metals, for which a systematic behaviour is found. Influxes due to metallic dust particles behave more like the elements of the first group. The origin of the impurities where this is known is given as well as details of the systematic behaviour, including differences due to the line-of-sight of the observing spectrometer. A clear difference is seen when the discharge fuel is H and this has implications for tritium and deuterium-tritium operations.